Nematodes as Sentinels of Heavy Metals and Organic Toxicants in the Soil - Ekschmitt, Klemens (The Society of Nematologists, 2006)
Field and laboratory research has repeatedly shown that free-living soil nematodes differ in their sensitivity to soil pollution. In this paper, we analyze whether nematode genera proved sensitive or tolerant toward heavy metals and organic pollutants in six long-term field experiments. We discuss overlaps between nematode physiological responses to heavy metals and to organic pollutants, which may explain why nematodes can exhibit co-tolerance toward several contaminants. We propose a simple method for separating direct effects of soil contamination on nematode populations from indirect effects mediated through the food chain. Finally, we analyze the extent to which nematodes exhibited consistent responses across the experiments analyzed. Our results show that (a) indirect effects of pollution were generally strong; (b) fewer nematode genera were tolerant than sensitive; (c) many genera, including practically all Adenophorea, exhibited a common response pattern to contaminants; and (d) several genera of the Secernentea exhibited differential tolerance toward particular pollutants. We conclude that bioindication of soil contamination should preferentially be based on tolerant, and less on sensitive, nematodes. We provide a list of nematode genera that may potentially serve as differential bioindicators for specific soil contaminants.